2007
DOI: 10.1152/ajprenal.00164.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronicl-arginine treatment in experimental hyperuricemia

Abstract: Experimental hyperuricemia (HU) results in preglomerular arteriolopathy, cortical vasoconstriction, and glomerular hypertension. Recently, uric acid has been shown to induce endothelial dysfunction. We therefore studied the effect of acute and chronic administration of l-arginine (a substrate for endothelial nitric oxide synthase) on the renal hemodynamic and vascular structural alterations induced by HU. To induce HU, oxonic acid (OA; 750 mg.kg(-1).day(-1)) was administered in male Sprague-Dawley rats. To stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 44 publications
0
94
0
Order By: Relevance
“…Experimental studies indicate direct and unfavorable effects of uric acid on vascular and renal biology [35,36,37,38,39]. Studies show that elevated uric acid concentrations cause endothelial dysfunction leading to the reduction in endothelial levels of nitric oxide and, thus, to renal vasoconstriction [40,41]. The influence of high uric acid concentration on vascular smooth-muscle cells is expressed through the intensification of cellular proliferation, inflammation and activation of the local renin-angiotensin system [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate direct and unfavorable effects of uric acid on vascular and renal biology [35,36,37,38,39]. Studies show that elevated uric acid concentrations cause endothelial dysfunction leading to the reduction in endothelial levels of nitric oxide and, thus, to renal vasoconstriction [40,41]. The influence of high uric acid concentration on vascular smooth-muscle cells is expressed through the intensification of cellular proliferation, inflammation and activation of the local renin-angiotensin system [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, SUA levels have been thought to be an important marker for ED and an early indicator of vascular injury in renal failure, HT and CVD (41,42). In a study using endothelial cell cultures, SUA decreased NO synthesis (43) and was shown to contribute to ED by gaining a pro-oxidative property (44,45). In ADPKD, the SUA levels increased as a result of a decrease in GFR (46)(47)(48) and high SUA levels were related to early onset HT and renal disease progression (49).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%
“…Experimentally increased uric acid levels result in accelerated renal-disease progression by variably increasing systolic BP, afferent glomerular arteriolopathy, oxidative stress, and endothelial dysfunction in different rat models, and administration of allopurinol reversed these deleterious effects (149,158). In addition, reduction of BP with enalapril and potentiation of NO with NOS substrate L-arginine also variably improved renal function (209,283). However, the role of uric acid as a risk factor for kidney disease is largely unknown (145).…”
Section: Nistala Et Al 2052mentioning
confidence: 99%